Potassium Alleviates Post-anthesis Photosynthetic Reductions in Winter Wheat Caused by Waterlogging at the Stem Elongation Stage - Gao, Jingwen; Su, Yao; Yu, Man; Huang, Yiqian; Wang, Feng; Shen, Alin (Frontiers in Plant Science, 2021)
Waterlogging occurs frequently at the stem elongation stage of wheat in southern China, decreasing post-anthesis photosynthetic rates and constraining grain filling. This phenomenon, and the mitigating effect of nutrient application should be investigated as it could lead to improved agronomic guidelines. We exposed pot-cultured wheat plants at the stem elongation stage to waterlogging treatment in combination with two rates of potassium (K) application. Waterlogging treatment resulted in grain yield losses, which we attributed to a reduction in the 1,000-grain weight caused by an early decline in the net photosynthetic rate (Pn) post-anthesis. These decreases were offset by increasing K application. Stomatal conductance (Gs) and the intercellular CO2 concentration (Ci) decreased in the period 7–21 days after anthesis (DAA), and these reductions were exacerbated by waterlogging. However, in the period 21–28 DAA, Gs and Ci increased, while Pn decreased continuously, suggesting that non-stomatal factors constrained photosynthesis. On DAA 21, Pn was reduced by waterlogging, but photochemical efficiency (ФPSII) remained unchanged, indicating a reduction in the dissipation of energy captured by photosystem II (PSII) through the CO2 assimilation pathway. This reduction in energy dissipation increased the risk of photodamage, as shown by early reductions in ФPSII in waterlogged plants on DAA 28. However, increased K application promoted root growth and nutrient status under waterlogging thereby improving photosynthesis post-anthesis. In conclusion, the decrease in Pn caused by waterlogging was attributable to stomatal closure during early senescence; during later senescence, a reduction in CO2 assimilation accounted for the reduced Pn, and elevated the risk of photodamage. However, K application mitigated waterlogging-accelerated photosynthetic reductions and reduced yield losses.